Run on your new legs. 3 - Midori, Wataru (Yen Press, 2022)
"Kikuzato finally meets Doujima, the first para-athlete--and adult--he's ever looked up to. But it turns out Doujima shares a complicated history with Kikuzato's prosthetist, Chidori. Meanwhile, Kikuzato's middle school friend Takegawa reminisces over the past after he's told to quit the soccer club, and the track-and-field club's competitions are brought to a halt by the COVID-19 pandemic!"--Provided by publisher.